Identification of Quantifiable Predictors of Relapse in Patients with Alcohol‐Associated Liver Disease. Issue 7 (13th March 2021) - Shen, Nicole T.; Kaplan, Alyson; Fahoum, Khalid; Basu, Elora; Shenoy, Akhil; Wahid, Nabeel; Ivatorov, Amanda; Pisa, Joseph; Salajegheh, Annaheta; Dawod, Enad; Rosenblatt, Russell; Fortune, Brett; et al.
Abstract : Abstinence in patients with alcohol‐associated liver disease (ALD) reduces mortality. Most predictors of relapse are not quantifiable, preventing objective analysis of relapse risk and targeted intervention to improve clinical outcomes. We prospectively enrolled patients with ALD from November 2016 to December 2019 and administered a survey with two previously published scales to assess insight into alcohol‐use disorder (Hanil Alcohol Insight Scale [HAIS]) and social support (Community Assessment Inventory Scale [CAIS]). Relapse was assessed using surveys and metabolite testing. Unadjusted and prespecified adjusted regression analyses identified predictors of relapse. We enrolled 81% of eligible patients (n = 136), of whom 58 had follow‐up data available at the time of analysis. Over a median follow‐up of 1 year (interquartile range: 0.5‐1.4), 10 patients relapsed (17%). Patients who relapsed were more likely to continue drinking despite either a diagnosis of liver disease or a decompensating event, and were less likely to have been transplanted (all P < 0.05). In unadjusted regression, the HAIS and the "support inside the home" subcategory of the CAIS were predictive of relapse, with odds ratio (OR) = 0.84 (95% confidence interval 0.72‐0.97) and 0.85 (0.74‐0.97). In adjusted regression, the HAIS was no longer significant, with adjusted OR = 0.70 (0.49‐1.00, P = 0.05), whereas the "support inside the home' subcategory of CAIS remained significant, with adjusted OR = 0.69 (0.51‐0.92, P = 0.01). Conclusions : Risk factors for relapse in patients with ALD were identified and quantified prospectively, suggesting opportunities to objectively identify patients at risk for relapse as well as to intervene to prevent relapse. Abstract : image